2014
DOI: 10.4028/www.scientific.net/amr.1082.123
|View full text |Cite
|
Sign up to set email alerts
|

Welding of Aluminum to DP600 Steel Plates by Refill Friction Stir Spot Welding Process (Refill FSSW): Preliminary Results

Abstract: The main objective of the current work was to produce sound Refill FSSW joints between AA6181-T4 aluminum and DP600 steel plates. The steel plates were used in two different surface conditions: with and without galvanized surface layer. The Taguchi statistical method was used to find out the set of parameters indicated to produce joint with higher mechanical resistance. Then, the possibility of joining these dissimilar metals using the Refill FSSW process was verified. Tool rotation speed and welding time were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In contrast volumetric defects have little influence on the shear strength of the joints. Verastegui et al [17] applied the Taguchi statistical method to find out the set of parameters indicated to produce a joint with higher strength. He found that the galvanised layers of sheet to be joined do not cause any substantial effect on joint strength.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast volumetric defects have little influence on the shear strength of the joints. Verastegui et al [17] applied the Taguchi statistical method to find out the set of parameters indicated to produce a joint with higher strength. He found that the galvanised layers of sheet to be joined do not cause any substantial effect on joint strength.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have used OFAT to select the ranges of process parameters for the main experiments. 14,15 Effertz et al. 14 employed the OFAT approach to examine the sensitivity of the friction spot welding process for a single change in the process and then applied the Taguchi method to the main experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Verastegui et al. 15 employed the OFAT approach for the friction stir spot welding process to obtain the optimum values of rotational speed, welding time, and tool penetration depth. This approach is time-consuming and increases the number of experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of the welding process parameters on the load capacity of joints and the weld microstructure has become the focus of much research investigation (Ref [5][6][7]. Oberembdt et al (Ref 5) concluded that the most effective variable for controlling joint strength is plunge depth.…”
Section: Introductionmentioning
confidence: 99%